Social Entrepreneurship, Nila Satria Banyumas Cooperative, Canvas Perspective on Islamic Business and Economic Models - Miatri Sholikhah; Dian Marjayanti (Perisai : Islamic Banking and Finance Journal, 2021)
The need for Muslim entrepreneurs / prospective entrepreneurs to be involved in solving the problem of poverty. One of them is by building social entrepreneurship that is in line with the principles of sharia economics and in accordance with the conditions of society's problems. In the field, there are various models of social entrepreneurship. With the conditions of dynamic community and organizational problems, it is possible to produce new social entrepreneurship models that can enrich existing social entrepreneurship models, especially those related to the context in Indonesia. However, studies related to social entrepreneurship models in Indonesia are still limited. Meanwhile, the discussion of social entrepreneurship with Islamic economics is only at the conceptual level. So that it does not provide an overview of the application of both. This study focuses on providing an overview of the social entrepreneurship model in the Nira Satria cooperative based on the business model canvas in the Indonesian context and the principles of Islamic economics. The research method is qualitative using literature data sources. The Nira Satria Cooperative Model is a community based social enterprise because 1) the user segment is members of the Nira Satria Cooperative as beneficiaries and consumers who use sugar ants, 2) Social value proposition is group empowerment in the form of individuals 3) managed by volunteers who come from cooperative members (farmers sugar) and NGOs. 4) the revenue comes from social / grants from the government and social institutions, and comes from mandatory membership fees. 5) Ownership and control schemes, namely collective and democratic. 6) has a sustainability goal. The description of the business model is in line with the principles of sharia economics.